BDNF and Cortisol in the Diagnosis of Cocaine-Induced Depression - Fonseca, Francina; Mestre-Pinto, Joan Ignasi; Rodríguez-Minguela, Rocío; Papaseit, Esther; Pérez-Mañá, Clara; Langohr, Klaus; Barbuti, Margherita; Farré, Magí; Torrens, Marta; , NEURODEP GROUP (Frontiers in Psychiatry, 2022)
Background: Major depressive disorders (MDD) and cocaine use disorders (CUD) are related with disability and high mortality rates. The assessment and treatment of psychiatric comorbidity is challenging due to its high prevalence, its clinical severity, mostly due to suicide rates, and the presence of medical comorbidities. The aim of this study is to investigate differences in Brain Derived Neurotrophic Factor (BDNF) and cortisol plasmatic levels in patients diagnosed with CUD-primary-MDD and CUD-induced-MDD, and also to compare them to a sample of MDD patients (without cocaine use), a sample of CUD (without MDD), and a group of healthy controls (HC) after a stress challenge. Methods: A total of 46 subjects were included: MDD (n=6), CUD (n=15), CUD-primary-MDD (n=16), CUD-induced-MDD (n=9) and 21 HC. Psychiatric comorbidity was assessed with the Spanish version of the Psychiatric Research Interview for Substance and Mental Disorders IV (PRISM-IV), and depression severity was measured with the Hamilton Depression Rating Scale (HDRS). Patients were administered the Trier Social Stress Test (TSST) before and after the biological measures, including BDNF and cortisol levels, were obtained. Results: After the TSST Cohen’s d values between CUD-primary-MDD and CUD-induced-MDD increased in each assessment from 0.19 in Post-TSST to 2.04 in Post-90-TSST. Pairwise differences among CUD-induced-MDD and both MDD and HC groups had also a large effect size value in Post-30-TSST and Post-90-TSST. In the case of the BDNF concentrations, CUD-primary-MDD and CUD-induced-MDD in Post-90-TSST (12627.27±5488.09 vs.17144.84±6581.06, respectively) had a large effect size (0.77). Conclusion: Results suggest a different pathogenesis for CUD-induced-MDD, with higher levels of cortisol and BDNF, compared to CUD-primary-MDD. Such variations should imply different approaches in treatment.